2019
DOI: 10.1213/ane.0000000000003538
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Hemodynamic and Echocardiographic Measurements Associated With Severe Right Ventricular Failure After Left Ventricular Assist Device Implantation

Abstract: Post-chest closure values of CVP and PAPi were significantly associated with severe RVF. Echocardiographic assessment of RV function post-CPB was weakly associated with severe RVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“… 7 After left ventricular assist device implantation, a PAPi cut‐off of 1.85 to 2.0 identified right heart failure. 8 , 9 , 10 , 11 Additional haemodynamic studies have shown that a lower PAPi portends increased RV filling pressures and impaired RV to pulmonary artery coupling. 16 In our PAH population, the established cut‐off value PAPi < 5.3 is much higher than in other disease populations, and pales in performance as a risk predictor (AUC 0.612 in PAH vs. 0.998 in RV infarction).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 7 After left ventricular assist device implantation, a PAPi cut‐off of 1.85 to 2.0 identified right heart failure. 8 , 9 , 10 , 11 Additional haemodynamic studies have shown that a lower PAPi portends increased RV filling pressures and impaired RV to pulmonary artery coupling. 16 In our PAH population, the established cut‐off value PAPi < 5.3 is much higher than in other disease populations, and pales in performance as a risk predictor (AUC 0.612 in PAH vs. 0.998 in RV infarction).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to predict RV failure in patients with acute inferior myocardial infarction 7 and after left ventricular assist device implantation. [8][9][10][11] Pulmonary artery pulsatility index as a risk predictor in PAH has also been investigated in a cohort comprising only idiopathic, familial, and anorexigen-associated aetiologies and found to be significantly associated with mortality. The main limitations of this study were narrow inclusion criteria, lack of echocardiographic correlates, and lack of contemporaneous data; data utilized for haemodynamic analysis was referenced from the National Institutes of Health Registry for Primary Pulmonary Hypertension, which was published in the 1980s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Right heart failure is a major cause of morbidity and mortality in patients undergoing left ventricular assist device implantation. PAPi has been evaluated pre‐operatively and intra‐operatively to predict the development of RHF in patients with left ventricular assist devices. The mean PAPi in patients who developed RHF after left ventricular assist device implant ranged from 1.3 ± 0.5 to 1.7 ± 0.3 and a PAPi threshold of 1.85 to identify patients at high risk of RHF has been proposed .…”
Section: Pulmonary Artery Pulsatility Indexmentioning
confidence: 99%
“…Since its first application in RV myocardial infarction, different patient groups were investigated. Apart from preoperative evaluation of LVAD planned patients, it was also examined intraoperatively during LVAD implantation 15 .…”
Section: Discussionmentioning
confidence: 99%